Study of Religiosity Animosity and Consumer Efficacy on Participation in Boycott Affiliation of Israeli Products: The Moderating Role of Xenocentrism - ramadania, Ramadania; Afifi, Muhammad Zaki; Haris, Didik Muhammad Nur; Taufiqurrahman, Abid; Syabanita Elida, Sri (ASEAN Marketing Journal, 2025)
Manuscript type: Quantitative paper Research Aims: To build and test the effects of religiosity animosity, consumer efficacy, and xenocentrism on boycott participation. Design/methodology/approach: This research uses a survey method with a sample of 255 young respondents in Indonesia, used surveys and interviews to collect data then analysis with SEM-PLS to examine the variables. Research Findings: The study found that several factors significantly influence boycott participation in products affiliated with Israel. First, religiosity animosity has a notable effect; higher levels of religiosity animosity are associated with an increased likelihood of boycott participation. Similarly, consumer efficacy—a consumer's belief in their power to make a difference—also positively correlates with boycott actions, suggesting that those with higher consumer efficacy are more inclined to participate in a boycott. Furthermore, xenocentrism, or the preference for foreign products and cultures, also has a positive relationship with boycott participation, indicating that individuals with higher levels of xenocentrism may be more likely to engage in such actions. Lastly, xenocentrism serves as a moderating factor, intensifying the effect of religiosity animosity on boycott participation, meaning that individuals with both high religiosity animosity and xenocentrism are more likely to participate in boycotts. Theoretical Contribution/Originality: This research contributes to the theoretical understanding of the concepts of religiosity animosity, consumer efficacy, and xenocentrism and their effects on consumer behavior, particularly in the context of boycott participation. Practitioner/Policy Implication: This research offers valuable insights for businesses, understanding the drivers of consumer boycotts—such as religiosity, animosity, and consumer efficacy—can help them address these concerns and potentially mitigate boycott participation. Policymakers can use these findings to grasp the root causes of consumer boycotts and work toward fostering improved relationships between different religious and cultural communities. Additionally, activists can benefit from a deeper understanding of how to effectively mobilize consumer boycotts, leveraging ethical and moral appeals to strengthen their campaigns' impact. Research limitation/Implications: This study has limitations in sample representativeness and reliance on quantitative data, which may hinder the generalizability and depth of insights into boycott motivations. Future research should address these by incorporating a more diverse sample, employing qualitative methods, and considering additional external factors like media influence and social campaigns to gain a fuller understanding of consumer boycott behavior